Towards a strategic tool for the business modeling of IDM startups : implementing the ADVISOR framework - Sharma, Ravi S. (2013)
This paper describes the ADVISOR online tool for Interactive Digital Media (IDM) Business modeling. The research objective was to develop an online business modeling tool for de-novo IDM firms based on the ADVISOR framework. The tool supports the business strategy of startups, incubators and new firms in the IDM marketplace such as content, applications and service providers. The core concept of the ADVISOR framework is that the value of a product or service offering in the digital marketplace is governed by the interaction among seven distinct components. The online tool that was implemented is based on the notions of value create and value capture described in the strategy literature. The field research suggests that it is useful to perform such a profile analysis on a yearly basis so as to benchmark and track the firm’s performance. This enables entrepreneurs to think in terms of what can bring about new opportunities and what can return back to the firm goodwill and revenue from the market.